Técnicas de instalaciones eléctricas, en viviendas populares y su incidencia en el aprendizaje de los moradores de Monte Sinaí del Cantón Guayaquil - Cardenas Burgos, Boanerges Lautaro (2023)
Nowadays, residential electrical installations acquire great importance due to the benefit they represent for humanity. This degree project talks about these benefits and importance, especially with regard to knowledge of electrical installations inside homes. This is an investigation with the definition of the facilities, the objective is for its main parts and components and safety, economy and flexibility, as its essential characteristics. All this in close relationship with what it can represent for the client or user. This research work has been structured in three fundamental parts: Introduction, where its methodological elements, foundation and projections are presented and introduced. Development that contains the information from the project exhibition on the regeneration and installation of the interior electrical system in the popular housing of Monte Sinaí, in the north of the city of Guayaquil, based on the theoretical aspects related to its indicators such as electrical science. , its principles, elements, operation, installation mode, precautions, dangers, accident prevention methods and other important details.